Alterations of RNA-binding protein found in neurons in Drosophila neurons and glia influence synaptic transmission and lifespan - Lin, Wei-Yong; Liu, Chuan-Hsiu; Cheng, Jack; Liu, Hsin-Ping (Frontiers in Molecular Neuroscience, 2022)
The found in neurons (fne), a paralog of the RNA-binding protein ELAV gene family in Drosophila, is required for post-transcriptional regulation of neuronal development and differentiation. Previous explorations into the functions of the FNE protein have been limited to neurons. The function of fne in Drosophila glia remains unclear. We induced the knockdown or overexpression of fne in Drosophila neurons and glia to determine how fne affects different types of behaviors, neuronal transmission and the lifespan. Our data indicate that changes in fne expression impair associative learning, thermal nociception, and phototransduction. Examination of synaptic transmission at presynaptic and postsynaptic terminals of the larval neuromuscular junction (NMJ) revealed that loss of fne in motor neurons and glia significantly decreased excitatory junction currents (EJCs) and quantal content, while flies with glial fne knockdown facilitated short-term synaptic plasticity. In muscle cells, overexpression of fne reduced both EJC and quantal content and increased short-term synaptic facilitation. In both genders, the lifespan could be extended by the knockdown of fne in neurons and glia; the overexpression of fne shortened the lifespan. Our results demonstrate that disturbances of fne in neurons and glia influence the function of the Drosophila nervous system. Further explorations into the physiological and molecular mechanisms underlying neuronal and glial fne and elucidation of how fne affects neuronal activity may clarify certain brain functions.